Crating y delivering winning advertising y marketing presentations - Moriarty, Sandra; Duncan, Tom (Illinois-USA: NTC Business Books, 1995)
Contents: the what, how, and why of business prsentations; presentation strategy; planning the message; selecting and planning the audiovisuals; designing the visuals; orchestrating the presentation; making the presentation; delivering your message; presentation follow-up.
Appendix: Planning cards slide planner p. 143/Storyboard format p. 144/Slide stryboard format p. 145/Master prsentation checklist p. 146/Index p. 150
Keywords: Marketing - Manual